2006
DOI: 10.1177/104063870601800306
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Dot Enzyme-Linked Immunosorbent Assay for Evaluation of the Immune Status to Canine Parvovirus and Distemper Virus in Adult Dogs before Revaccination

Abstract: Abstract. A growing body of literature has been published indicating that the current practice of annual vaccination of dogs may not be beneficial and in some cases may even be harmful. A number of publications have proposed assessing the immune status of dogs before annual revaccination. In this study the usefulness of a commercially available dot-ELISA kit was evaluated to determine the duration IgG antibody titers to canine parvovirus (CPV) and canine distemper virus (CDV) in 158 dogs vaccinated at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 11 publications
4
21
0
1
Order By: Relevance
“…The effect of maternally derived antibodies on the young population of dogs mostly sampled in this study and the nature of CDV can result in low or unsustainable immunity over a given period of time. This is also in agreement with what was reported in the literatures (Waner, 2004;Waner et al, 2004;Waner and Keren-Kornblatt, 2006).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The effect of maternally derived antibodies on the young population of dogs mostly sampled in this study and the nature of CDV can result in low or unsustainable immunity over a given period of time. This is also in agreement with what was reported in the literatures (Waner, 2004;Waner et al, 2004;Waner and Keren-Kornblatt, 2006).…”
Section: Discussionsupporting
confidence: 83%
“…Immunity induced tends to be relatively lower than in CPV. This is in conformity with what was reported in literature (Waner et al, 2004;Waner, 2004;Waner and Keren-Kornblatt, 2006). The test of hypothesis at P < 0.05 confirmed that there was a high significant association between level of immunity and vaccination against CPV and CDV antigens (p < 0.0001).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In practice, immunisation against CPV infection is usually based on repeated vaccination over a period of 6 to 18 weeks of age, without considering the maternal antibody titre (Nandi et al, 2009). Haemagglutination inhibition and ELISA are the most useful tests to assess the antibody level before vaccination (Waner et al, 2006). However, constant epidemiological supervision and sequence analysis of the CPV types will help clarify whether this mutant has become permanently established in the dog population and whether it is also spreading in other parts of the world, thus providing insights into the mechanisms driving the evolution of CPV-2.…”
Section: Discussionmentioning
confidence: 99%